Exploring Kelantanese syncretism: The Siamese influences in traditional Kelantanese interior design style (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Architecture syncretism involves the fusion of architectural elements from distinct cultures, combination between Siamese and Kelantanese stands out prominently. This research investigates Siamese influences, analysing their cultural meanings and implications on Kelantanese interior design. Siamese cultures managed to become the dominant influences in Kelantanese's life, although Siamese accounting only 1.18 per cent of the population. The arrival of Chinese traders intermarried with the Siamese led to the Peranakan Chinese community's development, resulting in more Chinese Siamese in Malaysia. Siamese culture assimilated with Malay culture creates unique, artistic, and architectural elements. However, modernization is causing these influences to fade, highlights the importance of studying Siamese elements in traditional Kelantanese interior design to preserve this culture and foster cross-cultural appreciation. The conceptual framework established focuses on the acculturated interior, aims to bridge the research gap in the field. This research utilised qualitative methods, comprising grounded theory, case studies, and simple ethnographic analysis. The findings reveal Istana Jahar in Kota Bharu has the most conspicuous syncretism between Siam and Kelantan in terms of architectural style in interior design, shaped by historical events between the Kelantanese and the rulers, including the kingdom of Siam and the colonial forces with the literature supports.